Comparison of Two Types of Insoles on Musculoskeletal Symptoms and Plantar Pressure Distribution in a Work Environment: A Randomized Clinical Trial - Almeida, Josiane S.; Vanderlei, Franciele M. [UNESP]; Pastre, Eliane C.; Martins, Rodrigo A. D. M.; Padovani, Carlos R. [UNESP]; Filho, Guaracy C. (Marshfield Clinic, 2016)
Background: The aim of the present study was to assess plantar pressure distribution and musculoskeletal symptoms following the use of customized insoles among female assembly line workers. Methods: The study included 29 female assembly line workers (age, 29.76 +/- 5.79 years; weight, 63.79 +/- 12.11 kg) with musculoskeletal symptoms who work predominantly while standing. The Nordic Musculoskeletal Questionnaire was administered to the study population. Plantar pressure was determined using a computerized plantar pressure feedback system. A control group (n=13) used ethylvinylacetate insoles (Podaly (R)) that were individually heat molded and heat glued. The intervention group (n=14) also used the insoles and a strip of the same material was added to the site of greatest plantar pressure as determined by the electronic feedback device. After five weeks, the plantar pressure data were collected again and the questionnaire was administered a second time. Results: There was no significant difference between groups with regard to pain in any anatomic site. However, within each group the lumbar region exhibited a reduction in symptoms in the intervention group (P<0.05), and the feet exhibited a reduction in symptoms in both groups (P<0.05). Mean plantar pressure increased and plantar surface decreased in the intervention group (P<0.05). Conclusion: Insoles increased foot comfort in both groups. However, the added strip did not significantly modify either plantar pressure or other symptoms in female workers.
Keywords: Worker health; Orthopedic devices; Foot